The Emerging Roles of Human Gut Microbiota in Gastrointestinal Cancer - Guo, Qianqian; Qin, Hai; Liu, Xueling; Zhang, Xinxin; Chen, Zelong; Qin, Tingting; Chang, Linlin; Zhang, Wenzhou (Frontiers in Immunology, 2022)
Gut microbiota is composed of a large number of microorganisms with complex structure. It participates in the decomposition, digestion and absorption of nutrients, promotes the development of immune system, inhibits the colonization of pathogens, and thus modulates human health. Especially, the relationship between gut microbiota and gastrointestinal tumor progression has attracted widespread concern. It is found that gut microbiota can influence gastrointestinal tumor progression in independent ways. Here, we focused on the distribution of gut microbiota in gastrointestinal tumors and further elaborated the impact of gut microbiota metabolites, especially short-chain fatty acids, on colorectal cancer progression. Additionally, the effects of gut microbiota on gastrointestinal tumor therapy were outlined. Finally, we put forward the possible problems in gut microbiota and gastrointestinal oncology field, and prospected the efforts we need to make.